Focusing Literary Trends of Dalit Literature in Indian Context - Kaur , Komalpreet (International Journal of Psychosocial Rehabilitation, 2020)
Indian Dalit writing, which can be followed back to a corpus of compositions from Maharashtra during the 1960s, alludes to writing of the abused, for the most part connected with an assorted gathering generally viewed as the least among the Indian populace and known as "untouchables." While Dalit writing created in light of worries explicit to Indian social and social history, in the course of the most recent 20 years Dalit writing has got itself a spot in the World Republic of Letters through interpretations into English. India is one of the quickest developing nations on the planet, yet, it is infamous for its unbending station framework. This writing shows sensational records of social political encounters of Dalit people group in the position based society of India. This paper checks the chronicled background of covering, condition of the smothered and beginning stage of Dalit works out. It joins the examination of improvement and degree of Dalit writing.